Data Mining Correlation Of Student Discipline With Level Of Achievement Using Apriori Method - Wahyuni, Windy Indah; Yusfrizal, Yusfrizal; Fatmaira, Zira (Journal of Engineering, Technology and Computing (JETCom), 2024)
Student discipline is the ability to follow the rules and carry out the tasks given. Discipline is one very important factor in determining the level of student achievement. Disciplined students have the skills necessary to get the job done and achieve their goals. There is a relationship between student discipline and the level of academic achievement achieved, students who have a good level of discipline tend to have a higher level of academic achievement than students who are less disciplined. Conversely, students who are less disciplined tend to have problems such as skipping school frequently, neglecting assignments, or causing disturbances in class. This can disrupt the learning process and affect students' ability to achieve optimal levels of achievement. From the 20 data tested, the best rule is produced, namely if the student's attendance is very good, and has a responsible, polite, and obedient nature, then the student is included in the top 10 class champions at school with a supporting value of 35%, a certainty value of 100%..